Resposta :
Resposta:
2x - y - 6 = 0
B (cordenada) = é o número independente que é o -6
A (abscissa) =
[tex] - \frac{b}{a} [/tex]
ou seja,
[tex] - \frac{ (- 6)}{2} [/tex]
resultado é 3
então, concluímos que
Y = -6
X = 3
![Ver imagem LEANDRO82829](https://pt-static.z-dn.net/files/d1c/c0c1294f56282c76d36d678c0bd8942a.jpg)
Resposta:
2x - y - 6 = 0
B (cordenada) = é o número independente que é o -6
A (abscissa) =
[tex] - \frac{b}{a} [/tex]
ou seja,
[tex] - \frac{ (- 6)}{2} [/tex]
resultado é 3
então, concluímos que
Y = -6
X = 3